Nickel‐ or Iron‐Catalyzed Cross‐Coupling of Aryl Carbamates with Arylsilanes. Issue 15 (3rd August 2016) - Shi, Wen‐Juan; Zhao, Hong‐Wei; Wang, Yang; Cao, Zhi‐Chao; Zhang, Li‐Sheng; Yu, Da‐Gang; Shi, Zhang‐Jie
Abstract: Aryl carbamates were for the first time applied as electrophiles in the cross‐coupling with arylsilanes via nickel or iron catalysis to construct valuable biaryl compounds. This new coupling reaction features a good group tolerance and non‐sensitivity to steric hindrance on both aryl carbamates and arylsilanes. Abstract :